Attenuated glucose uptake promotes catabolic metabolism through activated AMPK signaling and impaired insulin signaling in zebrafish - Xi, Longwei; Zhai, Gang; Liu, Yulong; Gong, Yulong; Lu, Qisheng; Zhang, Zhimin; Liu, Haokun; Jin, Junyan; Zhu, Xiaoming; Yin, Zhan; Xie, Shouqi; Han, Dong (Frontiers in Nutrition, 2023)
Glucose metabolism in fish remains a controversial area as many fish species are traditionally considered glucose intolerant. Though the energy homeostasis remodeling has been observed in fish with inhibited fatty acid β-oxidation (FAO), the effects and mechanism of the remodeling caused by blocked glucose uptake remains poorly understood. Here, we blocked glucose uptake by knocking out glut2 in zebrafish. Intriguingly, the complete lethality, found in Glut2-null mice, was not observed in glut2-/- zebrafish. Glut2-/- zebrafish that survived lived to adulthood and bred the maternal zygotic mutant glut2 (MZglut2) fish, which exhibited growth retardation, decreased blood and tissue glucose levels, and low locomotion activity. The decreased pancreatic β-cell numbers and insulin expression, as well as liver insulin receptor a (insra), fatty acids synthesis (chrebp, srebf1, fasn, fads2, and scd), triglycerides synthesis (dgat1a), and muscle mechanistic target of rapamycin kinase (mtor) of MZglut2 zebrafish, suggesting impaired insulin-dependent anabolic metabolism. Up-regulated expression of lipolysis (atgl and lpl) and FAO genes (cpt1aa and cpt1ab) in the liver and proteolysis genes (bckdk, glud1b, and murf1a) in muscle were observed in the MZglut2 zebrafish, as well as elevated levels of P-AMPK proteins in both the liver and muscle, indicating enhanced catabolic metabolism associated with AMPK signaling. In addition, decreased amino acids and elevated carnitines of the MZglut2 zebrafish supported the decreased protein and lipid content of the whole fish. In summary, we found that blocked glucose uptake impaired insulin signaling-mediated anabolism via β-cell loss, while AMPK signaling-mediated catabolism was enhanced. These findings reveal the mechanism of energy homeostasis remodeling caused by blocked glucose uptake, which may be a potential strategy for adapting to low glucose levels.